New species of Centris (Xanthemisia) Moure from the Mesoamerican Dominion and the Mexican Transition Zone (Hymenoptera: Apidae) - Vivallo, Felipe; Vásquez-Lenis, Elder A.; Mérida-Rivas, Jorge A. (Zootaxa, 2023)
Three new species of oil-collecting bees of the genus Centris (Xanthemisia) Moure are described and illustrated: C. jakalteka sp. nov., C. maya sp. nov. and C. purhepecha sp. nov. The new proposed taxa are distributed in the north of the Neotropical Region, specifically in the Mesoamerican Dominion and the Mexican Transition Zone, between the Neotropics and Nearctic. In addition, a distribution map and an identification key for the species of the subgenus occurring in the aforementioned regions are also presented.